2009
DOI: 10.1182/blood-2009-02-205815
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Rho GTPase activating protein p190-B enhances hematopoietic stem cell engraftment potential

Abstract: IntroductionHematopoietic stem cells (HSCs) are defined by their unique ability to give rise to all mature immune and blood cell lineages while at the same time regenerating themselves in a process termed "self-renewal" to sustain hematopoiesis throughout life. In addition, HSCs traffic throughout the body and possess the ability to reconstitute all hematopoietic lineages on transplantation into lethally irradiated mice, characteristics that have been used in therapeutic stem cell transplantation. [1][2][3] To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…PTPRS was expressed by a Since Ptprs -/-HSCs displayed increased repopulating capacity in vivo compared with Ptprs +/+ HSCs, this suggested that PTPσ might regulate processes involved in HSC engraftment or self renewal. We thus considered whether RAC proteins, a subset of RhoGTPases that are necessary for normal HSC engraftment capacity (14,15,19), might be regulated by PTPσ. In cell lines, it has been shown that PTPσ dephosphorylates and thereby activates p250GAP, a RhoGTPase that inhibits RAC protein activation (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTPRS was expressed by a Since Ptprs -/-HSCs displayed increased repopulating capacity in vivo compared with Ptprs +/+ HSCs, this suggested that PTPσ might regulate processes involved in HSC engraftment or self renewal. We thus considered whether RAC proteins, a subset of RhoGTPases that are necessary for normal HSC engraftment capacity (14,15,19), might be regulated by PTPσ. In cell lines, it has been shown that PTPσ dephosphorylates and thereby activates p250GAP, a RhoGTPase that inhibits RAC protein activation (20).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, BM cells from Ptprs -/-mice displayed markedly increased competitive repopulating capacity compared with Ptprs +/+ BM cells. The increased functional capacity of Ptprs -/-HSCs was associated with increased activation of the RhoGTPase RAC1 (14,15), and inhibition of RAC1 blocked the augmented migration capacity of Ptprs -/-cells. Furthermore, negative selection of human cord blood (CB) HSCs for PTPσ caused a 15-fold increase in repopulating capacity compared with human PTPσ + HSCs.…”
Section: Introductionmentioning
confidence: 92%
“…It has previously been shown that RAC1 (Cancelas et al, 2005) and CDC42 (Yang et al, 2007a) regulate HSC engraftment through acting on cell shape, localization and retention, and mobilization. Not only are the small GTPases themselves important, but upstream factors like DOCK2 (Kikuchi et al, 2008), ARH GAP5 (p190-B; Xu et al, 2009), ARH GEF7 (β-PIX; Reddy et al, 2016), or PTP RS (Quarmyne et al, 2015), or downstream factors such as PAK2 (Dorrance et al, 2013) and WASF2 (WAVE2; Ogaeri et al, 2009) also affect engraftment. Our study confirms these studies and adds that the niche regulates the generation of functional HSCs by modulating the activity of this pathway in HSCs not only through secretion of ligands such as the chemokine CXCL12 but also through modifications in the expression level of critical mediators of the pathway, such as β-PIX, DOCK2, and WAVE2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in contrast to rhoA knock-out in MEF cells (12), deletion of the GEF rgnef blocked focal adhesion formation (62). As mentioned above, deletion of the GAP p190B a major negative regulator of RhoA, led to increased long-term HSC activity and reduced progenitor activities (50), whereas rhoA knock-out resulted in a differentiation block from HSCs to blood progenitors. It is possible that in a complex process such as hematopoiesis, RhoA activity is tightly regulated by the interplay of multiple regulators.…”
Section: Signaling Function Of Rhoa Revealed By Gene-targeting Regulamentioning
confidence: 97%
“…Inhibition of RhoA activity by overexpressing dominant-negative mutant RhoA enhanced HSPC proliferation and engraftment (49). In contrast, increasing RhoA activity by knocking out of one of the major RhoA GAPs in the primitive HSPCs (p190B) also enhanced HSPC engraftment (50). These observations made it difficult to interpret the role of RhoA in regulating HSPCs in the suppression-of-function and gain-of-function models.…”
Section: Effector1mentioning
confidence: 99%